AL-AZHAR AND MODERATE: EXPLORING THE ROLE OF ALUMNI AL-AZHAR OF EGYPT IN STRENGTHENING UMMAH UNITY IN INDONESIA THROUGH THE CONCEPT OF "WASATHIYYAH" - Siswanto Siswanto; Ngadri Ngadri (Religio Education, 2022)
Religious moderation is a discourse echoed by the Indonesian government recently in the context of an effort to stem the thoughts of radicalism, terrorism and anarchism that can destroy the integrity of the Indonesian State. Al-Azhar Egypt is one of the leading and oldest religious institutions trying to bridge the multidimensional conflict tensions triggered by religious issues with its washatiyyah concept. This article attempts to explore the role of al-Azhar West Java (PAAM) alumni in spreading the dialogue of moderation of religion in West Java and the association of this organization with Al-Azhar Egypt. The author is actively involved in conducting observations and interactive interviews with figures and alumni of al-Azhar, West Java, through the ethnographic approach. Results of the discussion show that efforts to strengthen the washatiyyah azhari concept in the West Java region are carried out by supporting work programs in several fields, namely Education, Da'wah, Research and Development, Social, Community Relations, Information Technology.